2020
DOI: 10.1038/s41598-020-60868-9
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of CT radiomic features reflecting tumour heterogeneity according to image quality and image processing parameters

Abstract: The reliability of radiomics features (RFs) is crucial for quantifying tumour heterogeneity. We assessed the influence of imaging, segmentation, and processing conditions (quantization range, bin number, signal-to-noise ratio [SNR], and unintended outliers) on RF measurement. Low SNR and unintended outliers increased the standard deviation and mean values of histograms to calculate the first-order RFs. Variations in imaging processing conditions significantly altered the shape of the probability distribution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 38 publications
(57 reference statements)
2
28
0
Order By: Relevance
“…Interestingly, we found no significant correspondence between tumor volume (ml) and mutational status (Supplemental Table 3). Our results are consistent with those from Park et al (34) and Lee et al (35), testing the stability and reliability of radiomic features to evaluate tumor heterogeneity. Notably, Lee and collaborators (35), by studying the variability of radiomics features and their relationship with tumor size and shape upon 260 lung nodules, found that only a few features-including spherical disproportion and dissimilarity-showed high reproducibility in correlation with nodule status.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we found no significant correspondence between tumor volume (ml) and mutational status (Supplemental Table 3). Our results are consistent with those from Park et al (34) and Lee et al (35), testing the stability and reliability of radiomic features to evaluate tumor heterogeneity. Notably, Lee and collaborators (35), by studying the variability of radiomics features and their relationship with tumor size and shape upon 260 lung nodules, found that only a few features-including spherical disproportion and dissimilarity-showed high reproducibility in correlation with nodule status.…”
Section: Discussionsupporting
confidence: 93%
“…Another example is the use of radiomics, which is an emerging field of medical image analysis that utilizes radiological images to predict patient outcomes. It has been proposed that radiomics could be used to quantify tumor heterogeneity [ 84 , 85 ]. Since radiological images are frequently taken for diagnostic purposes, the ability to track tumor heterogeneity throughout tumor progression would be extremely valuable for furthering our understanding of tumor heterogeneity.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In feature selection, we selected 2 CTR features, Skewness and Kurtosis (6) based on histogram, and 2 PETR features, SUVmean and SUVmax 7, with high reproducibility for slice thickness condition changes. The study of stability and reproducibility of the radiomics features (6,7,(24)(25)(26)(27)(28)(29)(30)(31) shows multiple parameter changes (e.g., slice thickness) in general produces greater measurement errors. In this case, the selected 4 features only have good reproducibility against slice thickness.…”
Section: Discussionmentioning
confidence: 99%